2020
DOI: 10.1101/2020.06.29.20142984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic and genetic associations between anhedonia and brain structure in UK Biobank

Abstract: Background: Anhedonia is a core symptom of multiple psychiatric disorders and has been associated with changes in brain structure. Genome-wide association studies suggest that anhedonia is heritable with a polygenic architecture but few studies have explored the association between genetic loading for anhedonia - indexed by polygenic risk scores for anhedonia (PRS-anhedonia) - and structural brain imaging phenotypes. We investigated how anhedonia and polygenic risk for anhedonia were associated with br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…The pathways investigated here were previously found to be implicated in schizophrenia in both animal and human studies (4,17,53). In the current study, we were able to identify structural neuroimaging as well as clinical phenotypes associated with biologically informed PRSs, and these were shown to be more strongly associated with neuroimaging phenotypes than whole-genome PRS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The pathways investigated here were previously found to be implicated in schizophrenia in both animal and human studies (4,17,53). In the current study, we were able to identify structural neuroimaging as well as clinical phenotypes associated with biologically informed PRSs, and these were shown to be more strongly associated with neuroimaging phenotypes than whole-genome PRS.…”
Section: Discussionmentioning
confidence: 88%
“…Here, the axon gene-set was associated with thalamic radiations, white matter microstructural tracts that link the thalamus to the rest of the cerebral cortex (50), and volume of the parahippocampal gyrus, a cortical region that plays a role in memory processes such as encoding and retrieval (51). Both neuroimaging phenotypes have been implicated in schizophrenia (52), and have recently been associated with state anhedonia and PRS for anhedonia, a core negative symptom of schizophrenia (53). The findings here indicate that genes conferring risk for schizophrenia that are aggregated in the axon gene-set are strengthening evidence for brain structural regions that are already implicated in schizophrenia psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is involved in emotion regulation via limbic‐thalamo‐cortical projections (Ward, 2013), and previous research has reported positive correlations between optimism and left thalamic (Yang et al, 2013) and left nucleus accumbens volume in young adults (Dolcos et al, 2016). Similarly, anhedonia and lifetime major depressive disorder (MDD; negatively associated with wellbeing) are associated with smaller thalamus and nucleus accumbens volumes (Ancelin et al, 2019; Zhu et al, 2021). In terms of the caudate, a negative association between left caudate volume and subjective wellbeing ( n = 49, aged 12 years; Boyes et al, 2022) is supported by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a positive association between subjective wellbeing-PGS and thickness of right superior temporal gyrus and volume of insula (n = 585; Song et al, 2019) while another found no evidence of wellbeing-PGS mediation on hippocampal volume (n = 636 twins/siblings; van't Ent et al, 2017). PGS of anhedonia was also associated with reduced total GMV and thickness of para-hippocampal, superior temporal gyrus and insula (n = 19,592;Zhu et al, 2021). Furthermore, imaging genetic studies have shown that brain structural variations are under polygenic influence (Grasby et al, 2020;Smith et al, 2021), but whether genetic variants that influence brain structure overlap with those that influence wellbeing is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is very limited research into potential effects of rheumatoid arthritis (RA) on the brain. It is essential to investigate and monitor the role of cognition and brain phenotype differences that come with age as these can be a potentially early substrate of cognitive and psychological health Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%